Analisis Kualitas Isi dan Kalimat Efektif pada Teks Opini Dalam Website ”Taulebih” Edisi Desember 2023 Sebagai Literasi Edukasi Pendidikan Seksualitas dan Kesehatan Reproduksi Berdasarkan Nilai Agama - Wisnu Bima Prakoso; Yunanda Eka Novelianto; Jannatur Rohmah; Ayu Rahma Alfa Sania; Wenny Shafira Azzahra; Asep Purwo Yudi Utomo; Andi Naga Wulan (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This study analyzes the quality of content and ineffectiveness of sentences in opinion texts on the December 2023 edition of the "Taulebih" website as educational literacy for sexuality education and reproductive health based on religious values. This research uses two approaches, namely the methodological approach and the theoretical approach. The methodological approach uses a qualitative descriptive approach, while the theoretical approach uses a syntactic approach to analyze the quality of content and analyze effective sentences. Data collection techniques in this study used intensive reading techniques and note-taking techniques. The data that has been collected is then analyzed using the agih method. The presentation of data in the study was carried out by informal methods. Analysis of content quality and effective calibration on the opinion text on the December 2023 edition of the "Taulebih" website as educational literacy for sexuality education and reproductive health based on religious values also uses the presentation of data in tables to facilitate and clarify data analysis. The results of the content quality analysis are supported by strong and interconnected opinions and reasons from the opinion article. Meanwhile, the ineffectiveness of sentences in the opinion text "Taulebih" includes incompatibility of the characteristics of effective sentences, ambiguous sentences, waste of words or pleonasm, and spelling errors. This research adds new knowledge insight and critical sense in terms of analyzing the quality of content and effective sentences in an opinion text. It is hoped that this research can also be useful for readers in writing the right opinion text according to linguistic rules to produce good-quality sentences that are arranged effectively.